2012
DOI: 10.4236/psych.2012.312a164
|View full text |Cite
|
Sign up to set email alerts
|

Neuroplasticity and Positive Psychology in Clinical Practice: A Review for Combined Benefits

Abstract: Research on using positive psychological perspectives to drive brain plasticity in a positive direction is increasingly encouraging and empowering for clinicians and clients. Increased lifespan with neuroplastic gains was found by Diamond in lab rats when they were held and spoken to. Improvements in brain chemistry, architecture and performance associated with lifestyle choices are now being documented in humans with increasing frequency of reports. Positive psychology can strengthen this trend toward increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…There is evidence to suggest that use of Secondary strategies can be enhanced by improving a person's cognitive functioning. Cognitive training has been found to improve the positive neuroplasticity of a person's brain 46 . These activities appear to add new brain cells and in doing so cognitive abilities are improved.…”
Section: Components Of the Wwwpst Stress Management Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence to suggest that use of Secondary strategies can be enhanced by improving a person's cognitive functioning. Cognitive training has been found to improve the positive neuroplasticity of a person's brain 46 . These activities appear to add new brain cells and in doing so cognitive abilities are improved.…”
Section: Components Of the Wwwpst Stress Management Frameworkmentioning
confidence: 99%
“…Cognitive training has been found to improve the positive neuroplasticity of a person's brain. 46 These activities appear to add new brain cells and in doing so cognitive abilities are improved. There are many different gratitude intervention studies found that well-being was improved.…”
Section: Secondary Strategiesmentioning
confidence: 99%
“…Whereas, beliefs are "firmly held convictions" accepted as "true" without any empirical proof to determine the veracity of such beliefs. The neurological foundation for these particular violence-enhancing "cognitive" risk indicators (perceptions and beliefs) used in the SAVE programme is based in well-established neuroscience research which shows "mental activity correlates with neuronal activity" (Doidge, 2015;Goleman, 2013;Hanson, 2013;Schmid, 2013;Shaffer, 2012;Kurzweil, 2012;Siegel, 2011;Caporale and Dan, 2008;Fields, 2007). Furthermore, the brain uses experiencedependent neuroplasticity on a daily basis to form and reform new neural connections (Greenfield, 2014) as well as strengthen those cognitive pathways most often used due to the brain's basic operating principle of "neurons that fire together, wire together" (Hebb, 1949).…”
Section: Save Tool Suitementioning
confidence: 99%
“…This dynamic process allows us to learn from and adapt to different experiences. In the same vein, Shaffer (2012) indicates that neuroplasticity can be defined as the natural tendency of the brain architecture to shift in negative or positive directions in response to intrinsic and extrinsic influences. Strong connections exist between fluctuations of emotional states and brain functions.…”
Section: Introductionmentioning
confidence: 99%